2008
DOI: 10.1086/533468
|View full text |Cite
|
Sign up to set email alerts
|

Severe Renal Dysfunction and Risk Factors Associated with Renal Impairment in HIV‐Infected Adults in Africa Initiating Antiretroviral Therapy

Abstract: Despite screening, mild-to-moderate baseline renal impairment was relatively common, but these participants had greatest increases in eGFR after starting ART. Severe eGFR impairment was infrequent regardless of ART regimen and was generally related to intercurrent disease. Differences between ART regimens with respect to changes in eGFR through 96 weeks were of marginal clinical relevance, but investigating longer-term nephrotoxicity remains important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
128
8

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(156 citation statements)
references
References 28 publications
20
128
8
Order By: Relevance
“…Some patients with normal kidney function at baseline still progress to CKD stage ≥3 despite HAART, as documented in 1.9 and 1.6% of the patients participating in ALLRT and DART studies, respectively [28,59]. Thus, a kidney biopsy should also be considered in patients on HAART who develop signs of acute kidney injury, those who show progressive kidney failure during therapy, and in those in whom other potentially nephrotoxic drugs (besides those in a HAART regimen) are being used, and whose kidney function fails to improved upon discontinuation of the nephrotoxic agent [17].…”
Section: Limitationsmentioning
confidence: 99%
“…Some patients with normal kidney function at baseline still progress to CKD stage ≥3 despite HAART, as documented in 1.9 and 1.6% of the patients participating in ALLRT and DART studies, respectively [28,59]. Thus, a kidney biopsy should also be considered in patients on HAART who develop signs of acute kidney injury, those who show progressive kidney failure during therapy, and in those in whom other potentially nephrotoxic drugs (besides those in a HAART regimen) are being used, and whose kidney function fails to improved upon discontinuation of the nephrotoxic agent [17].…”
Section: Limitationsmentioning
confidence: 99%
“…23 A number of observational studies have documented TDF-associated nephrotoxicity following its widespread use in patients. [24][25][26] Four (10%) subjects in this study were suspected to have UTIs. Another study in Nigeria found an increased frequency of UTI in adolescents and young adults with HIV who had advanced clinical WHO stages.…”
Section: Discussionmentioning
confidence: 80%
“…This is especially apparent in HIV-infected persons with low CD4 counts and high HIV viral loads at the time of ART initiation and in those with preexisting kidney diseases such as HIVAN [18,19,20]. With the increasing availability of ART, the risk of ESRD in HIV patients has decreased by more than 50% in some populations [10].…”
Section: Overall Art Is Probably Beneficial For Kidney Functionmentioning
confidence: 99%